2016
DOI: 10.20472/te.2016.4.2.002
|View full text |Cite
|
Sign up to set email alerts
|

Trait Emotional Intelligence, Self-Confidence and Valuation of Mathematics: Mediation and Moderated Mediation Analyses of Summer Versus Regular Semester Students

Abstract: Abstract:Studies suggest trait emotional intelligence (EI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…This result was also supported by Ogundokun and Adeyemo (2010), Mavroveli and Sánchez Ruiz (2011) and Espinosa (2016) which found a positive relationship between trait EI and mathematical achievements. According to Kanhai (2014), there existed a relationship between emotional intelligence and students' maths achievements because the elements of emotional control and management could serve as predictors in maths and science grades.…”
Section: Trait Emotional Intelligencesupporting
confidence: 77%
See 4 more Smart Citations
“…This result was also supported by Ogundokun and Adeyemo (2010), Mavroveli and Sánchez Ruiz (2011) and Espinosa (2016) which found a positive relationship between trait EI and mathematical achievements. According to Kanhai (2014), there existed a relationship between emotional intelligence and students' maths achievements because the elements of emotional control and management could serve as predictors in maths and science grades.…”
Section: Trait Emotional Intelligencesupporting
confidence: 77%
“…For the acquisition of varied skills that foster educational success, positive emotions appeared to link to educational settings (Corradino & Fogartym, n.d.). This was supported by Espinosa (2016) which showed that trait emotional intelligence could improve students' confidence in mathematical problem solving abilities and students's attitude had positive impacts on the resulting outcomes. The findings in Espinosa (2016) were supported by Ogundokun and Adeyemo (2010), and Mavroveli and Sánchez-Ruiz (2011).…”
Section: Problem Statement and Objectivesmentioning
confidence: 78%
See 3 more Smart Citations